Implementasi geostrategi di dunia: strategi dalam menjaga kepentingan nasional - Batubara, Rizal Septian triputra (Maliki Interdisciplinary Journal, 2025)
Geostrategy is a multidimensional approach used by states to utilize geographical position, economic power, technological advances, and international relations to achieve national interests. This research discusses the dynamics of 21st century global geostrategy, highlighting the United States’ strategy through military alliances in the Indo-Pacific region, China’s Belt and Road Initiative project, and Indonesia’s implementation of the World Maritime Axis concept. In addition, contemporary issues such as cyberattacks, climate change, technological competition, and the influence of social media and renewable energy are analyzed as key elements in the transformation of modern geostrategy. The findings show that today’s geostrategy is no longer limited to military aspects, but includes diplomacy, economy, culture, and unconventional defense. Indonesia, with its strategic geographical location, has great potential to play an important role in the global arena through strengthening infrastructure, cyber resilience, defense industry, and soft power. This research concludes that a country that is able to integrate these various aspects in an adaptive and sustainable manner will be better prepared to face increasingly complex global geopolitical challenges.